The effect of performance demands on lower extremity biomechanics during landing and cutting tasks - Boyi Dai; William E. Garrett; Michael T. Gross; Darin A. Padua; Robin M. Queen; Bing Yu (Elsevier, 2019)
Background: Anterior cruciate ligament (ACL) injuries commonly occur during the early phase of landing and cutting tasks that involve sudden decelerations. The purpose of this study was to investigate the effects of jump height and jump speed on lower extremity biomechanics during a stop-jump task and the effect of cutting speed on lower extremity biomechanics during a side-cutting task. Methods: Thirty-six recreational athletes performed a stop-jump task under 3 conditions: jumping fast, jumping for maximum height, and jumping for 60% of maximum height. Participants also performed a side-cutting task under 2 conditions: cutting at maximum speed and cutting at 60% of maximum speed. Three-dimensional kinematic and kinetic data were collected. Results: The jumping fast condition resulted in increased peak posterior ground reaction force (PPGRF), knee extension moment at PPGRF, and knee joint stiffness and decreased knee flexion angle compared with the jumping for maximum height condition. The jumping for 60% of maximum height condition resulted in decreased knee flexion angle compared with the jumping for maximum height condition. Participants demonstrated greater PPGRF, knee extension moment at PPGRF, knee valgus angle and varus moment at PPGRF, knee joint stiffness, and knee flexion angle during the cutting at maximum speed condition compared with the cutting at 60% maximum speed condition. Conclusion: Performing jump landing at an increased jump speed resulted in lower extremity movement patterns that have been previously associated with an increase in ACL loading. Cutting speed also affected lower extremity biomechanics. Jump speed and cutting speed need to be considered when designing ACL injury risk screening and injury prevention programs. Keywords: ACL injury, Injury prevention, Kinematics, Kinetics, Loading mechanism, Risk factor